Computer Access Evaluations for Persons with Disabilities. - Heinisch, Barbara (1995)
Keywords: dept.sed; faculty_collection; sabbatical_report

The Role of Constructivism in the Mathematics Education of Learning Disabled Students. - Johnston, Elizabeth (1994)
Keywords: dept.sed; faculty_collection; sabbatical_report

Roads to Reading Disability: When Poor Readers Become "Learning Disabled" - Spear-Swerling, Louise (1993)
Keywords: dept.sed; faculty_collection; sabbatical_report

Case Studies on Teaching Special Needs and at-Risk Students. - Piazza, Robert (1992)
Keywords: dept.sed; faculty_collection; sabbatical_report

A Study of Methods of Integrating Whole Language Instruction and Direct Instructional Procedures. - Taylor, Maravene (1991)
Keywords: dept.sed; faculty_collection; sabbatical_report

Educating and Training the Mentally Retarded in Israel. - Levy, Irwin (Spring ; Special Education., 1990)
Keywords: dept.sed; faculty_collection; sabbatical_report

Perspectives on Learning Disabilities: Biological, Cognitive, Contextual - Sternberg, Robert J.; Spear-Swerling, Louise (Westview Press, 1999)
Keywords: Education; Learning disabilities; Learning disabilities; Learning disabled children; Physiological aspects; Constructivism (Education); Context effects (Psychology) in children; award_winner; dept.sed; faculty_collection

Teaching for Thinking - Sternberg, Robert J.; Spear-Swerling, Louise (Psychology in the classroom, 1996)
Keywords: Study and teaching; Thought and thinking; United States; United States; Creative thinking; dept.sed; faculty_collection

The road not taken: an integrative theoretical model of reading disability. - Spear-Swerling, L.; Sternberg, R.J. (Journal of learning disabilities, 1994)
This article describes a theoretical model of reading disability that integrates a wide range of research findings in cognitive psychology, reading, and education across the age and grade span. The model shows how reading disability relates to normal reading acquisition, and includes four possible patterns of reading disability: nonalphabetic readers, compensatory readers, nonautomatic readers, and readers delayed in the acquisition of word-recognition skills. We compare our model to the models of other investigators and argue that our model is especially useful to practitioners. Finally, we discuss some of the educational implications of the model.
Keywords: Adolescent; Adult; Child; Dyslexia; Education, Special; Educational Status; Humans; MLCS; MLOWN; Mental Recall; Phonetics; Verbal Learning; adolescent; adult; child; dept.sed; dyslexia; education; educational status; human; learning; phonetics; psychological aspect; recall; review

Off Track: When Poor Readers Become "Learning Disabled" - Spear-Swerling, Louise; Sternberg, Robert J. (Renewing American schools, 1996)
Autorías: Louise Spear-Swerling, Robert J. Sternberg. Año de publicación: 1996. Libro en Dialnet.
Keywords: Reading disability; United States; United States; Learning disabilities; dept.sed; faculty_collection